2002
DOI: 10.1016/s1534-5807(02)00206-x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Multiple Hearts in Mice following Deletion of β-catenin in the Embryonic Endoderm

Abstract: Using Cre/loxP, we conditionally inactivated the beta-catenin gene in cells of structures that exhibit important embryonic organizer functions: the visceral endoderm, the node, the notochord, and the definitive endoderm. Mesoderm formation was not affected in the mutant embryos, but the node was missing, patterning of the head and trunk was affected, and no notochord or somites were formed. Surprisingly, deletion of beta-catenin in the definitive endoderm led to the formation of multiple hearts all along the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
180
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(197 citation statements)
references
References 54 publications
12
180
1
1
Order By: Relevance
“…Moreover, it has been shown that β-catenin is also essential for definitive endoderm formation 36 . We demonstrate here that Sox17 continuously expresses in the stomach and intestine during organogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that β-catenin is also essential for definitive endoderm formation 36 . We demonstrate here that Sox17 continuously expresses in the stomach and intestine during organogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus deletion of β-catenin in the endoderm promotes cardiac differentiation leading to ectopic heart formation [26]. Activation of β-catenin signaling, however, is required for in vitro cardiac myogenesis and differentiation [27].…”
Section: Discussionmentioning
confidence: 99%
“…An additional control was WT/Cre. Genotyping was performed with PCR using specific primers as described previously (7,33,54). Mer-Cre-Mer expression levels, determined by immunoblotting with an anti-Cre antibody, were equal in the ␤-catenin fl/fl /Cre versus WT/Cre mice (data not shown).…”
Section: Methodsmentioning
confidence: 98%
“…The breeding scheme for conditional deletion of ␤-catenin involved crossing the ␤-catenin fl/fl mouse obtained from Jackson Laboratories (7,33) with the heterozygous Mer-Cre-Mer mouse. The latter expresses Cre flanked by two modified estrogen receptors that are responsive to tamoxifen (54).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation